EVALUATION OF QUALITY OF ARTERIAL HYPERTENSION CONTROL IN POPULATION OF VOLOGDA REGION - A. I. Popugaev; G. Т Banshikov; A. A. Kolinko; N. A. Korolenko; R. A. Kasimov; Д. А. Rybakov; А. М. Kalinina (Рациональная фармакотерапия в кардиологии)
Aim. To study results of registration, calculation and evaluation of quality of arterial hypertension (HT) control (HT Register) in Vologda Region (VR).Material and methods. HT Register system is developed and legislatively introduced in the VR. Blood pressure registration in every visitor of out-patient clinics is the basic principle of HT Register. The algorithm of HT diagnosis in primary medical care of rural public health services was developed. Analysis of results of HT Register implementation in VR during 2004-2007 is presented.Results. Patients with HT stage 1 seek medical help more often in cities while patients with HT stage 3 seek medical help more often in villages. Patients with HT in villages take antihypertensive drugs more often, but they have more risk factors and associate conditions.Conclusion. Improvement of HT pharmacotherapy was observed in urban and rural districts of VR. At the same time non pharmacologic HT control has to be developed.